The Effect of Triceps Pressdown and Seated Rowing Exercises on Muscle Strength - Rahmatika, Zelika Miftahul; Prasetyo, Yudik; Yacshie, Betrix Teofa Perkasa Wibafied Billy; Hartanto, Amri; Arianto, Afeb Chesa (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The aim of the study was to determine the effect of the triceps press down, seated rowing and endurance exercise method on increasing arm muscle strength. A 2 x 2 factorial method was used. The research sample was 24 participants. The pull up test instrument for endurance and the digitec bow holding test were used. ANOVA was used for data analysis Î± = 0.05. Results are as follows (1) there is a significant difference between the triceps press down exercise and the seated rowing exercise on the increase in arm muscle strength. (2) There is a significant difference between athletes who have high and low muscle endurance on the increase in arm muscle strength. (3) There is a significant interaction between triceps press down exercise and seated rowing exercise with muscle endurance (high and low) on arm muscle strength in archery athletes.